Intensity of perinatal care for extreme preterm births and neurodevelopmental outcomes at age 5½: the EPIPAGE-2 cohort study - François Goffinet; Babak Khoshnood; Pierre-Yves Ancel; Monique Kaminski; Jennifer Zeitlin; Laetitia Marchand-Martin; Marie-Laure Charkaluk; Veronique Pierrat; Xavier Durrmeyer; Catherine Gire; Andrei Scott Morgan; Sabrina Twilhaar; et al. (BMJ Paediatrics Open)
Objective To explore the impact of intensity of perinatal (‘survival-focused’) care on outcomes at 5½ years for two groups of survivors: those born at 24–26 and at 27–28 weeks of gestation.Design Prospective, population-based national cohort.Setting France, 2011.Patients Children surviving to 5½ years who were born at <29 weeks gestation.Interventions Intensity of perinatal care, defined at the hospital level, categorised into three based on the ratio of babies of 24–25 weeks of gestation admitted into neonatal intensive care to the number of fetuses alive at maternal admission to hospital subsequently delivered at 24–25 weeks gestation.Main outcome measures Neurodevelopmental disability (NDD—none, mild, moderate or severe) comprising cognitive, behavioural, sensory and motor abilities.Results Among 3217 births, 472 children born at 24–26 weeks and 633 born at 27–28 weeks survived. At 24–26 weeks, compared with children born in low-intensity hospitals, children born in high-intensity hospitals had the lowest levels of mild (33.9%) and moderate–severe (21.9%) NDD (ORs 0.42, 0.20–0.88 and 0.47, 0.20–1.12, respectively); no difference was found between hospitals of low and medium intensity. At 27–28 weeks of gestation, no differences were seen between hospitals of any intensity level (p=0.75).Conclusions No evidence was found to support concerns that survival-focused perinatal care is associated with increased long-term NDDs in children born extremely preterm or at a higher gestational age.